Mechanical Behavior of Materials : Engineering Methods for Deformation, Fracture, and Fatique - DOWLING, Norman E. (Prentice Hall, 1993)
Mechanical Behavior of Materials : Engineering Methods for Deformation, Fracture, and Fatique